Clinical outcomes of maternal and neonate with COVID-19 infection - Multicenter study in Saudi Arabia - Abdulrahman Al-Matary; Faeza Almatari; Mariam Al-Matary; Alaa AlDhaefi; Mohammed Hassan S. Alqahtani; Emad Ahmad Alhulaimi; Shahad AlOtaiby; Khowlah Almehiny; Lincy Soosan John; Faisal Samah Alanazi; Aisha Mansoor Ali; Faisal K. Aldandan (Elsevier, 2021)
Background: To this end, the influence of COVID-19 on pregnant women and their neonates is not completely clear. Therefore, the main aim of this study is to investigate maternal and neonatal clinical outcomes with confirmed COVID-19 infection. Besides, it investigates the likelihood of vertical transmission of COVID-19 infection from pregnant women to their neonates. Methods: A retrospective descriptive study was conducted in three medical centers during the period from March to November 2020. Data were collected from the available medical records in the respective hospitals using a standardized questionnaire on maternal and neonatal clinical outcomes. All pregnant women with confirmed COVID-19 infection across the three hospitals and their neonates were eligible to participate in this study. Descriptive statistics were presented as a median and interquartile range (IQR) or frequencies and percentages as appropriate using SPSS 24.0 software. Results: This study has identified a total of 288 pregnant women with confirmed COVID-19 infection over the study period of a median age of 30 years and median GA at diagnosis 38 weeks (IQR: 39 -33) as well as 27% of them were obese (n = 78). The majority of pregnant women were symptomatic with cough (n = 92, 31.9%) being the most frequent COVID-19 symptom followed by fever and dyspnea (n = 36, 12.5%). Two-hundred and four pregnant delivered (70.84%) and caesarean sections were prevalent among 35.8% of them. The most common adverse pregnancy outcome was premature (n = 31, 15.5%), followed by fetal distress (n = 13, 6.5%), preeclampsia (n = 4, 2.0%), and one pregnant woman died. The laboratory results exhibit that temperature higher than 38 (n = 27), leukopenia (n = 19), neutropenia (n = 54), ALT (n = 12), AST (n = 31), and thrombocytopenia (n = 35) were less frequent among pregnant women while lymphopenia (n = 126), hemoglobin levels lower than 13.0 (n = 218), deceased albumin levels (n = 195) were most frequent among them. However, a small proportion of pregnant women were admitted to the ICU (3.8%). The most frequent maternal treatments were antibiotics (n = 81), antiviral (n = 49), and corticosteroid (n = 24). Of 204 neonates, four had died and all the remaining neonates were alive. The median gestational age at delivery was 39 weeks (IQR: 35-40). Most neonates had normal laboratory results. However, 14 had lymphopenia (7.0%), 22 had neutropenia (11.0%), and 11 had thrombocytopenia (5.5%). Four infants had low hemoglobin levels of less than 13.0 (2.0%) and 81 had hyperbilirubinemia (e.g., total bilirubin of higher than 23; 40.5%). Approximately less than one-half of neonates required admission to the NICU (n = 86, 43%), 7% of them required respiratory support of mechanical ventilation, and none of them get infected with COVID-19 disease. Conclusion: This multicenter study suggests that the majority of pregnant women had mild or moderate disease symptoms. Nevertheless, this study did not find any evidence of possible vertical transmission of COVID-19 infection from mothers to their babies. This study may provide a baseline for further studies focusing on investigating long-term maternal and neonate's outcomes and possible vertical transmission of COVID-19 from mothers to their newborn babies.